Building of post-resection defects of the femoral bone in treatment of patients with metastatic lesions - Vyrva, Oleg; Golovina, Yanina; Subbota, Igor (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The authors analysed different variants for building post-resection defects of the femoral bone, revealed shortcomings and causes of complications after application of some methods of surgical interventions. The use of different variants for building post-resection defects of long bones is biomechanically grounded and indications for each surgical intervention are determined.